Child Grants Programme in Nepal: Issue of Affordability and Sustainability - Bhoosal, Yam Lal; Paudel, Kamal (Journal of Social Protection, 2024)
Nepal is committed to protecting human rights and ensuring social protection for all citizens, including children. This paper provides an overview of the existing child grant programme, which is aimed at social protection and improving health outcomes by addressing malnutrition, based on desk review and secondary data. The findings show that existing child grant contributes to the nutritional intake and promotes enrollment in the vital registration system, however, the distribution modality and governance of child grant distribution need to be revisited to link the actual beneficiaries with unique national identification.As per the latest population census of 2021, out of the total child population (10 million), the child grant programme covers approximately 14.9 percent. At present, the programme is operational in 25 districts, leaving nearly 50 per cent of children under the age of five in the remaining 52 districts outside its coverage. Despite this limitation, the government prioritised the enrollment of Dalit communities nationwide within this social protection initiative. To enhance its impact, the programme must be extended to cover the remaining districts and in all communities, aligning with national priorities and capacity to ensure effective implementation. This paper critically assesses the programme before its proposed expansion to additional districts as one of the government’s priority initiatives. Further, it advocates for the integration of fragmented social protection programmes for strengthening the next generation, foster human capital, and enhance public trust. Such integration would support the development of a citizen centric, responsive, accountable, and transparent government system by leveraging reliable and secure data exchange mechanism. This could be done by integrating the National ID with the child grant beneficiaries so that system will automatically verify and the entire verification process is changed from document-based verification to data-based verification.